Counselling Education as a Tool for Liberation and Sustainable Development among Secondary School Students in Ibadan - Oyelade, Oyekola Olukayode; Ojuolape, Mumud Olabode (NIU Journal of Humanities, 2026)
Secondary school students' education for emancipation and sustainable development is greatly aided by counselling education. The development of students' critical thinking, self-awareness, autonomy, and capacity for making wise choices that release them from social, psychological, and intellectual constraints is a key component of education for liberation. In contrast, the goal of sustainable development in education is to provide students with lifetime skills that promote economic productivity, social responsibility, and personal development. In order to improve liberation-oriented learning and sustainable development among secondary school students in Ibadan, Nigeria, this research looked at counselling education.  The study design used was a descriptive survey. Secondary school pupils from a few Ibadan public schools made up the population. A multistage sampling procedure was used to choose a sample of 200 students. A standardised questionnaire called the "Counselling Education, Liberation and Sustainable Development Questionnaire (CELSDQ)" was used to gather data. Experts in educational psychology and guidance and counselling validated the instrument, and Cronbach Alpha was used to determine its reliability.  The results showed that students' self-awareness (78%), decision-making skills (72%), academic engagement (75%), and career consciousness (82%) are all considerably improved by counselling education. Additionally, study shown that counselling services lower maladaptive behaviours that impede sustainable growth (68%) and increase emotional stability (70%). Additionally, it was shown that counselling education equips students with life skills that facilitate future productivity (74%) and social adjustment (80%). The research came to the conclusion that counselling education is a crucial tool for attaining education for sustainable development and emancipation in secondary schools. To improve student empowerment and development, it was suggested that the government and school officials bolster counselling services, hire more trained counsellors, and include counselling programs into school curriculum. Keywords: Secondary school students, self-awareness, decision-making, education for liberation, counselling education, sustainable development, and Ibadan